1994
DOI: 10.1128/jb.176.1.198-205.1994
|View full text |Cite
|
Sign up to set email alerts
|

Translation initiation factor IF1 is essential for cell viability in Escherichia coli

Abstract: Translation initiation factor IF1 is a highbly conserved element of the prokaryotic translational apparatus. It has been demonstrated earlier that the factor stimulates in vitro the initiation phase of protein synthesis. However, no mutation in its gene, infA, has been identified, and a role for IF1 in translation has not been demonstrated in vivo. To elucidate the function of IFi and determine if the protein is essential for cell growth, the chromosomal copy of infA was disrupted. Cell viability is maintai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
64
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 27 publications
2
64
0
Order By: Relevance
“…It is noteworthy that the newly identified rpoS-dependent genes do not appear to be essential genes as defined by Gerdes et al (26), except for infA (18), a finding consistent with the lack of major effects of the rpoS mutation on cell viability. To confirm the results of the whole-genome expression analysis, we performed RT-PCR experiments on a selection of differentially expressed genes belonging to each functional category (Fig.…”
Section: Vol 186 2004 Gene Expression At the Onset Of Stationary Phsupporting
confidence: 66%
“…It is noteworthy that the newly identified rpoS-dependent genes do not appear to be essential genes as defined by Gerdes et al (26), except for infA (18), a finding consistent with the lack of major effects of the rpoS mutation on cell viability. To confirm the results of the whole-genome expression analysis, we performed RT-PCR experiments on a selection of differentially expressed genes belonging to each functional category (Fig.…”
Section: Vol 186 2004 Gene Expression At the Onset Of Stationary Phsupporting
confidence: 66%
“…Ejection of IF1 consequently opens the A-site for incoming aminoacyl-tRNAs. In vivo studies have shown that IF1-depleted cells have low growth rates and short polysomes (39). These data demonstrate that IF1 is essential for cell viability and suggest that one or more of its functions are crucial.…”
Section: Translation Initiation Factorsmentioning
confidence: 77%
“…infA, infB, and infC are required for translation initiation and are also essential in E. coli (17,25) and S. aureus (22). The status of the infC gene in B. aphidicola BSg, initially annotated as a pseudogene due to the absence of a translation start codon (80), was recently changed (28) because, as in other enteric bacteria, it possesses an unusual AUU initiator codon.…”
Section: Main Features Of the Minimal Setmentioning
confidence: 99%